"Objection, Your Honor": Use of Social Media by Civilians to Challenge the Criminal Justice System. (June 2020) - Lev-On, Azi; Steinfeld, Nili
Social media constitute useful and effective platforms for miscarriage of justice campaigners to challenge state authorities and decisions taken by the criminal justice system. To characterize such endeavors, this study analyzes the activity in such a major group dedicated to the murder case of Tair Rada and the trial of Roman Zadorov, one of the most controversial legal cases in Israel's history. Using digital data extraction and linguistic analysis tools, we focus on five themes: (1) the central role of group administrators in directing the discourse and setting the group agenda; (2) correspondence of group activity with off-line events and mainstream media coverage; (3) skewed distribution of post publications per user and engagement measures per post; (4) prominent topics in group discussions, revolving around key figures, institutions and officials, making justice, considering alternative theories and examining investigative and forensic materials; and (5) the framing of key figures, institutions, and values in portraying a somewhat dichotomous image of a corrupted justice system, an innocent man wrongly convicted and a Facebook group in the search for the truth.